Peran Media Massa terhadap Perilaku Ibu dalam Upaya Pencegahan Demam Berdarah pada Rumah Tangga di Kota Yogyakarta - Asniati Djaswadi Dasuki, Hari Kusnanto (Berita Kedokteran Masyarakat (BKM), 2008)
Background: The  incidence of  dengue hemorrhagic  fever  (DHF)  is  increasing dramatically  especially  in  tropical areas. DHF can cause death.  It  is predicted  that 25  thousand people die every year because of DHF. Control of DHF  through fogging and use of abate can reduce population of Aedes  aegypti mosquitos but  it is costly and use in  improper  dosage  can  cause  resistance  to  insecticide. The  best way  to  prevent  the  disease  is  eradicating vector  larvae  through  3 activities  (draining, burying  and covering). Such efforts  can be  done by mothers  in  their household. Meanwhile  in  doing  these efforts mothers may  be  influenced  by some  factors,  i.e. mass media, knowledge and  attitude of mothers about DHF.Objective: The  objective  of  the  study  was  to  identify factors  related  to mothers’  behavior  in  preventing hemorrhagic  fever  in  the  household.Method: This was an  observational  study with cross  sectional design. The  sample of  the study was as many as  100 mothers. Data were  collected  through  questionnaires  and  analyzed  using  univariate,  bivariate  and multivariate  techniques.Result: Variable  of  role  of mass media was  statistically  significant  as  predictor  of DHF  prevention  behavior (p<0.05) with moderate  relationship  level  (r=0.352).  Variables  of  knowledge  and  attitude were  statistically significant with p<0.05  but  they  had negative  relationship.Conclusion: Mass media can  significantly  affect mothers’  behavior  in  preventing DHF  in  the  household.Keywords: mass media,  knowledge, attitude, DHF,  prevention